Peran Pasar Modal Syariah dalam Mendorong Ekonomi Islam - Dini Selasi; Dede Kuswandi; Wira Untung Supriyanto (Jurnal Nuansa : Publikasi Ilmu Manajemen dan Ekonomi Syariah, 2024)
The aim of this research is to find out how the sharia capital market affects the sharia economy. This research was conducted through a qualitative literature study, where the author collected data from various journal articles, books and other sources. The results of this research found that Islamic capital markets promote Islamic economics by incorporating ethical ideals into economic operations, resulting in a more inclusive and stable ecosystem. Profit and loss sharing used in several sharia capital market instruments including mudharabah and musyarakah encourages better risk management.